Avaliação da somatotropina bovina recombinante (rbST) nos não-componentes da carcaça de cabritos de três genótipos - Rodrigues, Luciana [UNESP]; Gonçalves, Heraldo César [UNESP]; Medeiros, Brenda Batista Lemos; Menezes, Jakilane Jacque Leal; Maestá, Sirlei Aparecida [UNESP] (Universidade Federal de Goiás, 2013)
This study was developed with the aim of evaluating recombinant bovine somatotropin (rbST) on non-carcass components of goat kids of three genotypes. It was used 23 male goat kids of three genotypes, being 8 Alpine, 4 ½ Boer + ½ Alpine (½ BA) and 11 ¾ Boer + ¼Alpine (¾ BA), from which 12 received rbST e 11 control. The growth hormone used was the recombinant bovine somatotropin (rbST) and animals of treatment 1 received the hormone in the amount of 0.3 mg/kg live weight, from 45 days, adjusted in intervals of 14 days. Animals of treatment 2 (control) received saline solution in the same dosage and interval. The ½ BA goats presented a higher proportion of external non-carcass components (head, feet and skin) in relation to Alpine goats. Regarding the vital organs, such as lungs, kidneys and spleen, and the non-carcass components blood, internal fat and perinephric fat, Alpine goats presented higher values than ¾ BA goats. The administration of recombinant bovine somatotropin (rbST) did not produce effect on proportions and weight of non-carcass components. Proportions and weight of non-carcass components varied in function of genotypes, although animals were slaughtered at similar live weight.

Desenvolveu-se o presente estudo com o objetivo de avaliar a somatotropina bovina recombinante (rbST) nos não-componentes da carcaça de cabritos de três genótipos. Foram utilizados 23 machos inteiros de três genótipos, sendo oito Alpino (A), quatro ½ Boer + ½ Alpino (½ BA) e 11 ¾ Boer + ¼ Alpino (¾ BA), dos quais 12 receberam rbSTe 11controle. O hormônio de crescimento utilizado foi a somatotropina recombinante bovina (rbST) e os animais do tratamento 1 receberam o hormônio na quantidade de 0,3 mg/kg de peso vivo, a partir dos 45 dias, ajustada em intervalos de 14 dias. Os animais do tratamento 2 (controle) receberam solução salina na mesma dosagem e intervalo. Os animais ½ BA apresentaram uma maior proporção dos não-componentes externos (cabeça, patas e pele) em relação aos da raça Alpina. Em relação aos órgãos vitais, como pulmão, rins e baço, e aos não-componentes sangue, gordura interna e gordura perirenal, os animais da raça Alpina apresentaram maiores valores em relação aos ¾ BA. A administração da somatotropina bovina recombinante (rbST) não produziu efeito nos não-componentes da carcaça. As proporções e os pesos dos não-componentes da carcaça variaram em função dos genótipos, embora abatidos a pesos vivos semelhantes.
Evaluation of recombinant bovine somatotropin (rbST) on non-carcass components of goat kids of three genotypes
Keywords: caprinos; componentes do peso vivo; hormônio de crescimento; rendimento de carcaça; carcass; goats; growth hormone; live weight components